TEACHERS’ NONVERBAL COMMUNICATION IN ENGLISH TEACHING AND LEARNING PROCESS - Antika, Rindilla; Ikhsan, Muhammad (Universitas PGRI Sumatera Barat, 2018)
Nonverbal communication is one of the communication types which are done in teaching and learning process. This research aims to analyze nonverbal communication types done by teachers in English teaching and learning process in SMP Negeri 10 Padang. It is a descriptive research in which the participants are two English teachers which taught at VII Grade SMP Negeri 10 Padang. The data were collected through observation checklist and field note and were analyzed by using Schmitz’s (2012) nonverbal communication theory. The result of the research shown that teacher at VII Grade SMP Negeri 10 Padang used nonverbal communication types such as Kinesics; using movement, Vocalics; using voice and intonation, and Proxemics; using distance, however, the teachers did not use Haptics, using touch, in English teaching and learning process. In conclusion, English teachers at VII Grade SMP Negeri 10 Padang had used nonverbal communication types and applied them in teaching and learning process.